Analisis Parenting Siti Aminah Pada Masa Golden Age Nabi Kajian Tafsir Tematik Ayat-Ayat Parenting - Ermita Zakiyah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
Parenting studies are an interesting topic to discuss, because everyone goes through that phase after getting married and having children, parenting is a new thing and full of challenges in proportion to the more intense Muslims want to study prophetic parenting as a guide for Muslims, namely parenting in the style of the Prophet who will be applied in everyday life. The purpose of this study is to look at the concept of Islamic parenting which is different from the concept of modern psychology. Nowadays, many working mothers cannot take care of their children full 24 hours, so that the golden age of children cannot maximize their time with a working mother where this is actually the same as the Prophet who was cared for by Halimatus Sa'diyah in his golden age and wasnot treated by siti Aminah, so this study is interesting. Muslims examine the concepts contained in the Qur'an with many approaches, parenting problems are studied with the thematic interpretation study of the Qur'an with the library research method or library research descriptively taking primary data sources in the form of parenting verses, Data analysis using the maudhuí method , by explaining the verses that fit the same theme